Pharmacognostical standardization of Hugonia mystax l. Roots - G. PENCHALA PRATAP,; G. SUDARSANAM,; V. NAGARAJU, (International Journal of Pharma and Bio Sciences, 2016)
The present study brings detailed pharmacognostical profile of roots of Hugonia mystax L. The species, H. mystax has a restricted global distribution, occurring only in India and Sri Lanka. Within India, it has been recorded in Maharashtra (Between Malvan and Vengurla), Karnataka (Dakshina and Uttara Kannada) Tamil Nadu (Plain, Foothills, and almost all districts) and Andhra Pradesh (Foothills, some of the districts like Nellore, Chittoor and Kurnool districts). It is an unexplored medicinal plant in the Indian medicinal system. According to ethnobotanical information, the root powder of H. mystax is used as the best antidote, anthelmintic, febrifuge and for the treatment of peptic ulcers. The problem encountered in the standardization of this medicinal plant is its identification by source. In these circumstances, pharmacognostical studies on roots of H. mystax have been undertaken mainly with this object in view. In the present study roots of H. mystax were subjected for Macroscopical, Microscopical, Physicochemical, Phytochemical, Fluorescence and H.P.T.L.C. analysis. In the microscopical studies, the different cell structures and arrangements were studied. Physicochemical parameters like the loss of drying, total ash value, acid insoluble ash, water insoluble ash, various extractive values etc., were carried out. Further, qualitative tests for various functional groups like Triterpenoids, Alkaloids, Glycosides etc..., were carried out and H.P.T.L.C. profile was also established with Methanolic extract. The Microscopical, Macroscopical, Phyto-chemical, Physico-chemical, screening on the roots of H. mystax furnish useful information for identification and authentication of the plant.